2011
DOI: 10.1292/jvms.10-0329
|View full text |Cite
|
Sign up to set email alerts
|

Footpad Dermatitis in Broiler Chickens in Japan

Abstract: ABSTRACT. The prevalence of footpad dermatitis (FPD) in broiler chickens in Japan was investigated. In the first examination at slaughterhouses, lesions were commonly observed on the footpads of a total of 8,985 broiler chickens from 45 flocks on 36 farms. In 3 flocks, all the birds examined had lesions. In the other 42 flocks, the incidence of FPD ranged from 31.9% (81/254) to 99.5% (1/222). The footpad lesions were classified into 4 categories according to the severity of dermatitis as follows; score 0, 1,18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
4
17
0
1
Order By: Relevance
“…However, bird activity decreased with age in this study, supporting the study of Weeks et al (1994), which might be due to increased body weight and a greater incidence of lameness with age (Kestin et al, 2001). Hashimoto et al (2011) detected FPD in Japanese broilers from 7 days of age and found that it worsened with age.…”
Section: Effects Of Hay Bales and Perches On Broiler Behaviorsupporting
confidence: 91%
See 1 more Smart Citation
“…However, bird activity decreased with age in this study, supporting the study of Weeks et al (1994), which might be due to increased body weight and a greater incidence of lameness with age (Kestin et al, 2001). Hashimoto et al (2011) detected FPD in Japanese broilers from 7 days of age and found that it worsened with age.…”
Section: Effects Of Hay Bales and Perches On Broiler Behaviorsupporting
confidence: 91%
“…Therefore, the presence of hay bales and perches may be beneficial to the welfare of slow growing strains, such as Japanese broilers. Hashimoto et al (2011) observed that the incidence of FPD ranged from 31.9% to 99.5% in broiler farms, and concluded that FPD represents a major welfare and production problem in the Japanese broiler production system. In comparison, the prevalence of FPD in the Netherlands, France, Portugal, and the United Kingdom is 38.4%, 70%, 70%, and 14.8%, respectively (Pagazaurtundua and Warriss, 2006;Allain et al, 2009;Gouveia et al, 2009;De Jong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Litter moisture was determined according to the Litter Humidity Determination Degree Method (BRASIL, 1992), with samples collected from two randomly selected locations in each quadrant. Pododermatitis lesions were scored according to a 0-3 scale as: score 0, no lesion; score 1, lesion covered less than 50% of the footpad; score 2, lesion covered 50-100% of the footpad; and score 3, lesion covered 100% of the footpad (Hashimoto et al, 2011). During pododermatitis scoring, footpad surface temperature (FPST, ºC) of each individual bird was registered to assess inflammation.…”
Section: Methodsmentioning
confidence: 99%
“…The severity of pododermatitis was scored in a 0-3 scale (0= no lesion; 1=lesion covering less than 50% of the footpad area; 2=lesion covering 50-100% of the footpad area; and 3=lesion covering 100% of the footpad area, including the digits), as proposed by Hashimoto et al (2011). Hock lesion was determined as present (skin redness) or absent (skin with homogeneous color).…”
Section: Data Recordingmentioning
confidence: 99%